Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper takes stock of Indonesia's performance against the original macroeconomic objectives under the IMF's extended arrangement. The paper compares the performance of the Indonesian economy in the post-crisis period with that of the other major 'crisis' countries in the region. It reviews the background to the current extended arrangement and describes the core macroeconomic objectives of the program. The paper also considers Indonesia's performance against objectives for growth, inflation, the balance of payments, and improving Indonesia's debt sustainability.